DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC METHOD FOR QUANTITATIVE ESTIMATION OF LAFUTIDINE IN BULK AND PHARMACEUTICAL DOSAGE FORM - Kumar, Ritesh; Chandra, Amrish; Gupta, Swati; Gautam, Pawan Kumar (International Journal of Applied Pharmaceutics, 2017)
Objective: The objectives of the present research was to develop a simple, precise, economical, accurate, reproducible and sensitive method for the quantitative estimation of lafutidine in bulk and its pharmaceutical dosage forms by Ultra Violet (UV) absorption spectrophotometry. Methods: The method uses 0.1 N HCl, pH 1.20 as a solvent of choice for the quantitative estimation of lafutidine in bulk and its tablets dosage form by UV absorption spectrophotometry at a wavelength of 290 nm. The method was validated for parameters like linearity, range, precision, Limit of Detection (LOD), Limit of Quantification (LOQ), accuracy, recovery and stability of the analyte. Results: Lafutidine exhibited absorbance maxima at 290 nm in 0.1 N HCl, pH 1.20 solvent. The developed method was validated as per the ICH validation guidelines. Beer's law was obeyed in range of 0-30 µg/ml with r2= 0.9997. The LOD and LOQ values of lafutidine were found to be 0.545 µg/ml and 1.654 µg/ml respectively. The mean % recovery for the developed method was found to be in the range of 99.25 to 99.45 % respectively for the marketed dosage forms. The developed method was also found to be robust. Conclusion: The developed method was found suitable for the routine quantitative analysis of lafutidinein bulk and pharmaceutical dosage form. It was also concluded that developed UV spectrophotometry method was accurate, precise, linear, reproducible, robust and sensitive.